The Magdeburg confession : 13th of April 1550 AD - Colvin, Matthew; Trewhella, Matthew (North Charleston, SC : CreateSpace, 2012)
"In 1548, Charles V imposed his infamous Augsburg Interim which was an attempt to smash the Protestant Reformation. While all of Protestant Germany conformed to his decree, one city decided to take a stand and resist his authority -- the city of Magdeburg. The pastors of Magdeburg issued their Confession and Defense of the Pastors and Other Ministers of the Church of Magdeburg on April 13, 1550 AD. Five months after issuing their Confession, Charles V's forces marched on Magdeburg. The people of Magdeburg burned everything outside the city walls and closed the city gates. The siege of Magdeburg had begun."--Cover, page 4.
Includes bibliographical references.
Keywords: Magdeburg Confession; Luther, Martin, -- 1483-1546 -- Political and social views; Government, Resistance to -- Religious aspects -- Lutheran Church -- History of doctrines -- 16th century; Government, Resistance to -- Germany -- History -- 16th century; Lutheran Church -- Doctrines -- History -- 16th century